Pengaruh Pengetahuan Produk terhadap Keputusan Pembelian Produk Kosmetik - Yofina Bintang Cahyani; Amelia Pristian Syah Putri; Fitria Damayanti; Fitri Ariani; Rokhmad Thoriqul Hidayat; Didit Darmawan (STIKes Ibnu Sina Ajibarang, 2025)
This study was conducted to assess the extent to which product knowledge influences consumer decisions in purchasing cosmetics by adopting a qualitative methodology with a literature study approach. This study includes the presentation of several scientific literatures, references, and theories that are closely related to the research variables. This study analyzes ten studies that focus on the study variables. The data analysis technique is carried out descriptively qualitatively in order to understand the relationship between the two variables. Based on the results of the analysis that has been carried out regarding the influence of product knowledge on purchasing decisions for cosmetic products, a positive relationship was found between the two. The study of consumer decisions in purchasing cosmetics is an interesting topic because this decision is one of the main challenges for cosmetic companies in determining the right marketing strategy. The complexity of the consumer decision-making process shows that many factors are interrelated and need to be considered. Therefore, companies need the ability to control the dynamics related to consumer behavior and adjust their business strategies to remain relevant. Understanding trends and changes in consumer purchasing patterns is an important thing that should not be ignored if the company wants to develop sustainably in the future.